Measuring overconfidence in inventory management decisions. Issue 3 (September 2016) - Ancarani, A.; Di Mauro, Carmela; D'Urso, Diego
Abstract: Overconfidence has emerged as a significant explanation of behaviour in diverse managerial settings. In this paper, we explore the relevance of overconfidence for supply chain management by running a series of human experiments within the framework of the classic Beer Game. Unlike previous experimental studies, participants were knowledgeable about supply chain management, either being graduate students in Operations Management or purchasing professionals. Results of the study support the view that overconfidence may lead supply chain professionals to be less careful in the management of inventories and thus incur more costs. A first implication for organizations is that purchasing professionals should be trained to discount their expectations of success by removing this optimistic bias. A second is the importance of providing managers and employees with benchmarks that allow them to assess correctly their performance in relative terms. The study also underlines the effect of environmental uncertainty as an important contextual factor influencing overconfident behaviour. Highlights: We explore the relevance of overconfidence for supply chain management. Overconfidence may lead supply chain professionals to incur more costs. Purchasing professionals should be trained to discount their expectations of success.